S-adenosylhomocysteine promotes endothelial dysfunction and activation : a role for hypomethylation in vascular disease - Barroso, Maria Madalena H. Serras Vicente, 1986- (2015)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2015